The Effect Of Product Innovation And Lifestyle On Brand Trust, Customer Satisfaction And Repurchase Intention - Ade Kurniawan; Parlagutan Silitonga (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of product innovation and lifestyle on brand trust, customer satisfaction and repurchase intentions at Pizza Hut Restaurants in the West Jakarta area. The population in this study were all customers of Pizza Hut Restaurants in the West Jakarta area. This study involved 230 respondents who were collected using questionnaire distribution with purposive sampling technique. Data analysis was carried out using Structural Equation Modeling (SEM) with the help of Smart-PLS software. The results of this study indicate that product innovation has a positive and significant effect on brand trust, customer satisfaction and repurchase intentions. In addition, lifestyle also has a positive and significant effect on brand trust, customer satisfaction and repurchase intentions. Brand trust has a positive and significant influence on customer satisfaction. Customer satisfaction has a positive and significant influence on repurchase intentions. Thus, product innovation and lifestyle play an important role in efforts to create brand trust, increase customer satisfaction and encourage customer repurchase intentions.